The Origin and Evolution of Antistasin-like Proteins in Leeches (Hirudinida, Clitellata). (18th November 2020) - Iwama, Rafael Eiji; Tessler, Michael; Siddall, Mark E; Kvist, Sebastian
Abstract: Bloodfeeding is employed by many parasitic animals and requires specific innovations for efficient feeding. Some of these innovations are molecular features that are related to the inhibition of hemostasis. For example, bloodfeeding insects, bats, and leeches release proteins with anticoagulatory activity through their salivary secretions. The antistasin-like protein family, composed of serine protease inhibitors with one or more antistasin-like domains, is tightly linked to inhibition of hemostasis in leeches. However, this protein family has been recorded also in non-bloodfeeding invertebrates, such as cnidarians, mollusks, polychaetes, and oligochaetes. The present study aims to 1) root the antistasin-like gene tree and delimit the major orthologous groups, 2) identify potential independent origins of salivary proteins secreted by leeches, and 3) identify major changes in domain and/or motif structure within each orthologous group. Five clades containing leech antistasin-like proteins are distinguishable through rigorous phylogenetic analyses based on nine new transcriptomes and a diverse set of comparative data: the trypsin + leukocyte elastase inhibitors clade, the antistasin clade, the therostasin clade, and two additional, unnamed clades. The antistasin-like gene tree supports multiple origins of leech antistasin-like proteins due to the presence of both leech and non-leech sequences in one of the unnamed clades, but a single origin of factor Xa and trypsin + leukocyte elastase inhibitors. This is further supported by three sequence motifs that are exclusive to antistasins, the trypsin + leukocyte elastase inhibitor clade, and the therostasin clade, respectively. We discuss the implications of our findings for the evolution of this diverse family of leech anticoagulants.